Assessment of effectiveness of the empiric treatment regimen in tuberculosis patients suspected with multiple drug resistance in the Russian Federation - Sergey A. Sterlikov; Anastasiya G. Samoylova; Vadim V. Testov; Konstantin A. Glebov; Irina A. Vasilyeva (Туберкулез и болезни лёгких, 2018)
The article presents the comparative assessment of effectiveness of tuberculosis treatment with empiric chemotherapy regimen IV. The outcomes of treatment with empiric regimen IV of the cases in whom later drug resistance was confirmed were compared with the outcomes of regimen IV prescribed to the patients who had confirmed resistance at least to rifampicin. The outcomes of empiric treatment with regimen IV in the cases without confirmed resistance to rifampicin were compared to outcomes of treatment with regimens I, II, and III, prescribed to those sensitive to rifampicin. No statistically significant differences in the number of favorable treatment outcomes were found which allows concluding that it is advisable to prescribe empiric regimen IV if multiple drug resistant tuberculosis is suspected.